EVALUATE OF LIVER CIRRHOSIS BY THE APRI INDEX IN KASAI SURGERY TO TREAT CONGENITAL BILIARY ATRESIA TYPE III (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the degree of cirrhosis of the pediatric patients treated with Kasai surgery atthe National Children’s Hospital through the APRi index.Subjects and Methods: A retrospective descriptive study of a 172 patients diagnosed with congenitalbiliary atresia, treated by Kasai surgery with extensive hilar fibrosis at National Children’s Hospitalfrom January 2016 to December 2020.Result: The mean APRi index before surgery was 1.77±1.43. Mean APRi score re-evaluated after1 month was 1.9± 4.34 and the mean APRi after 6 months was 1.71±2.9. Comparison of APRiscores before surgery and 6 months after surgery showed a statistically significant difference with p< 0.0001.Conclusion: The APRi index before surgery and 6 months after surgery is closely related to themortality rate after Kasai surgery to treat congenital biliary atresia in children.
Keywords: Kasai, APRi, biliary atresia.